Pengaruh Budaya Kerja Dan Motivasi Kerja Terhadap Semangat Kerja Karyawan STMIK Surya Intan - Aida Rohmah (Dinar Islamic Review, 2022)
This research is based on factors that cannot be ignored related to employee morale, namely work culture and work motivation. This can be reflected in the lack of employee morale because the work culture and work motivation between leaders and staff are still lacking, this can be seen from the discipline of working hours which is still far from what is expected of employees at STMIK Surya Intan. This study aims to determine the effect of work culture on the motivation and morale of STMIK Surya Intan employees. In this study using a quantitative approach, with a sample of 40 respondents. The sampling technique in this study used a purposive sampling technique. Data analysis in this study uses inferential statistics. Data that meets the requirements for analysis are processed using the SmartPLS3 program. From the test it was found that work culture has an effect on motivation, work culture has no effect on employee performance, and motivation has a positive effect on employee performance. Suggestions/recommendations, STMIK Surya Intan related to work culture requires satisfaction, discipline, work results, appreciation, so that employees can quickly complete work, regarding work motivation needs to be increased through education, through promotions, and through mutations, regarding work enthusiasm is needed improvement of employee work culture and employee motivation.